Anal atresia, coloboma, microphthalmia, and nasal skin tag in a female patient with 3.5 Mb deletion of 3q26 encompassing SOX2. Issue 6 (23rd April 2013) - Salem, Nabeel J.M.; Hempel, Maja; Heiliger, Katrin‐Janine; Hosie, Stuart; Meitinger, Thomas; Oexle, Konrad
Abstract A full term female newborn presented with prominent forehead, bilateral microphthalmia, iris coloboma and cataract, wide intercanthal distance, large, low‐set and protruding ears, skin tag at the left nasal nostril, imperforate anus with rectovestibular fistula, and postnatal growth delay with brachymicrocephaly. A marker chromosome was not detectable and the copy number of 22q11 was normal. However, array CGH revealed a 3.5 Mb microdeletion of chromosome region 3q26.32–3q26.33 (chr. 3: 178, 598, 162–182, 114, 483; hg19) which comprised the SOX2 gene. While SOX2 haploinsufficiency is known to cause microphthalmia and coloboma, it has not been described before in patients with anal atresia. © 2013 Wiley Periodicals, Inc.